2013
DOI: 10.1007/s12520-013-0120-0
|View full text |Cite
|
Sign up to set email alerts
|

Fallow deer (Dama dama dama) management in Roman South-East Britain

Abstract: This paper presents new carbon, nitrogen and sulphur isotope data for European fallow deer (Dama dama dama) in Roman Britain and discusses results in light of evidence from classical texts, landscape archaeology, zooarchaeology and the limited available samples of metric data. The new isotope data presented here are from Fishbourne Roman Palace (Sussex), two sites on the Isle of Thanet (Kent) and a further two sites in London. In spite of small sample sizes the data make an important contribution to the very l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 37 publications
1
31
0
1
Order By: Relevance
“…Carbon and nitrogen isotope signatures of bone and antler are now often used to reconstruct the ecological conditions in which ancient deer lived, to track past habitat changes in the vicinity of the sites of recovery, and to infer past human management practices . They are also used to define isotopic baselines with which human isotope signatures can be compared .…”
Section: Bone and Antler Structure And Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon and nitrogen isotope signatures of bone and antler are now often used to reconstruct the ecological conditions in which ancient deer lived, to track past habitat changes in the vicinity of the sites of recovery, and to infer past human management practices . They are also used to define isotopic baselines with which human isotope signatures can be compared .…”
Section: Bone and Antler Structure And Compositionmentioning
confidence: 99%
“…Researchers often consider antler and bone δ 13 C and δ 15 N values collectively; however, at present the question of whether bone and antler isotope signatures are equivalent and directly comparable has not been thoroughly addressed. A large body of research shows that individuals of all species yet studied are not isotopically homogeneous, with different body tissue having different isotopic ratios within individuals on constant diets depending on turnover rate and tissue composition .…”
Section: Bone and Antler Structure And Compositionmentioning
confidence: 99%
“…Analize izotopa ugljenika uglavnom se koriste za proučavanje ljudske i životinjske ishrane, međutim, razne studije pokazuju i njihov potencijal za rekonstrukciju stategija stočarstva i lova, upravljanje stadima, korišćenje pejzaža i rekonstrukciju lokalnog okruženja (Hammond and O'Connor 2013;Pilaar Birch 2013;Stevens et al 2013;Madgwick et al 2013;Doppler et al 2015). Princip na kome se zasniva rekonstrukcija ishrane podrazumeva razlikovanje vrednosti ugljenika (δ 13 C) kod biljaka koje na različit način vrše fotosintezu (C 3 i C 4 biljke) ili razlikovanje kopnenih i vodenih biljaka (DeNiro and Epstein 1978, 495, 505).…”
Section: A P 757unclassified
“…In Peru, Finucane, Agurto, and Isbell (2006) suggested that elevated δ 13 C in mice was due to consumption of seaweed from coastal sources. Madgwick et al (2013) (Madgwick et al 2013). Isotopic analysis of carbon, nitrogen, and sulphur can be used to effectively identify halophytic foods in palaeodiet.…”
Section: New Isotopes In Conjunction With Old Isotopesmentioning
confidence: 99%